Pedagogical leadership practices at the university. - Domínguez Maldonado, Julio (2015)
Objective: To characterize the  predominant style of leadership in/the managers/directors from their  own perspectives and their teachers  from the Engineering of the  University of Chile, Talca  Headquarters, 2014. Method: This research was  conducted based on a quantitative  approach, aimed at understanding  the leadership style that prevails in  the race directors of Engineering of  the University of Chile, home Talca,  from the perspective of the  protagonists and of their teachers.  The designed is characteristic of the  method of case study is a valuable  research tool and its greatest  strength ¡is that through if is  measured and recorded the behavior  of the people involved in the  phenomenon studied (Yin, 1989). The approach to each of the units  under study to collect information  organized from a primary source  (questionnaire) applied to the  Directors/Managers of the races  were the masterful design and ten  (10) teachers in each of these  academic units, of which leadership  styles were analyzed from their own  perspectives and their teachers. Results: The analysis of numerous  research and studies in the context  of educational organizations, check  the existing link between the smooth  functioning of educational institutions  and the proper exercise of the  management function or the  leadership of the principal or the  principal. That is why those who  coordinate and direct activities within  an educational organization, le  educational managers must be  aware of the innovations in the field  of management frequently occur.  Research in the educational context  and various experiences at national  and international level in this area,  emphasize that the key to improving  the quality of education is not only in  improving the education system  inputs, but also on the ability of  organization of educational  institutions.    Conclusions: The analysis was  made of headmasters and teachers  administered questionnaire shows  that the leadership style of the  Directors / Managers, more than a  decade of gestation of the University  of Chile, has developed a  breakthrough new to management  styles, participatory institutions